2007
DOI: 10.1038/sj.jid.5700824
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Activates Human Monocytes and Prevents Apoptosis

Abstract: Monocytes play a critical role in chronic atopic dermatitis (AD) and are the primary leukocytes that interact with activated platelets. Although activated platelets release a variety of mediators, the role of platelets in cutaneous allergic inflammation remains unclear. Serotonin (5-hydroxytryptamine, 5-HT) is one of the prototypic mediators produced by activated platelets. We examined the effect of 5-HT on the function and lifespan of human monocytes. Normal human monocytes treated with 5-HT exhibited upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 46 publications
2
91
0
Order By: Relevance
“…In this study, we confirm that colon (and spleen) CD103 + CD11c + DCs express the 5-HT 7 receptor. Previously, it has been shown that 5-HT induces phosphorylation of ERK1/2 and activation of NF-kB in monocytes (69). By using the 5-HT 7 receptor antagonist SB-269970, we showed that stimulation of LPS-matured CD11c + spleen DCs isolated from WT colitic mice with 5-HT upregulated IL-12p40, IL-1b, and IL-6 secretion via 5-HT 7 receptor signaling.…”
Section: Cd11cmentioning
confidence: 72%
“…In this study, we confirm that colon (and spleen) CD103 + CD11c + DCs express the 5-HT 7 receptor. Previously, it has been shown that 5-HT induces phosphorylation of ERK1/2 and activation of NF-kB in monocytes (69). By using the 5-HT 7 receptor antagonist SB-269970, we showed that stimulation of LPS-matured CD11c + spleen DCs isolated from WT colitic mice with 5-HT upregulated IL-12p40, IL-1b, and IL-6 secretion via 5-HT 7 receptor signaling.…”
Section: Cd11cmentioning
confidence: 72%
“…Alternatively, the presence of serum factors could modulate or synergize with 5HT, and it might have caused an overestimation of the 5HT influence. In an effort to avoid these potentially confounding issues, we have carried out all experiments on macrophages maintained in serum-free medium for 48 h. Thus, apart from the cell type-specific nature of 5HT actions, the distinct medium used for assaying 5HT might explain the discrepancy between the lack of effect of 5HT on IL-10 release seen in our experiments and those of others (20,49) and the positive action of 5HT in IL-10 production described in human alveolar cells and monocytederived dendritic cells (22,23). Despite these discrepancies, our results are in agreement with the lack of effect of 5HT 2 agonists on the LPS-induced monocyte cytokine production (21).…”
Section: Discussionmentioning
confidence: 92%
“…For example, human monocytes primed by LPS through binding to TLR4 respond to 5-HT by increasing their secretion of critical pro-inflammatory peptides, including IL-1β, IL-6, IL-8, IL12p40 and TNF-α [139]. In addition, 5-HT has also reported to inhibit monocyte apoptosis via the 5-HT1 and 5-HT7 receptors allowing monocytes to remain in tissues and to promote inflammation [143]. Other cells like eosinophils and mast cells respond to 5-HT by migrating whereas dendritic cells respond by up-regulating expression of IL-6 [139,144].…”
Section: Natural Killer and Natural Killer T Cells In Liver Fibrogenementioning
confidence: 99%